2013
DOI: 10.1021/jm400798j
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Data: Assessment, Predictions, Concordance, and Implications

Abstract: Could high-quality in silico predictions in drug discovery eventually replace part or most of experimental testing? To evaluate the agreement of selectivity data from different experimental or predictive sources, we introduce the new metric concordance minimum significant ratio (cMSR). Empowered by cMSR, we find the overall level of agreement between predicted and experimental data to be comparable to that found between experimental results from different sources. However, for molecules that are either highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Several measures are available to evaluate the similarities of kinase drug targets [15, 46, 7982], including sequence, structure, and inhibitor properties. For drug discovery purposes, experimental binding data regarding cross-reactivity of inhibitors may be the most relevant, although this data may be generated in different ways, with diversity arising from choice of binding or activity assays, conditions, target protein form, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Several measures are available to evaluate the similarities of kinase drug targets [15, 46, 7982], including sequence, structure, and inhibitor properties. For drug discovery purposes, experimental binding data regarding cross-reactivity of inhibitors may be the most relevant, although this data may be generated in different ways, with diversity arising from choice of binding or activity assays, conditions, target protein form, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Kinome-wide profiling data allow the creation and evaluation of computational models not only for activity but also selectivity predictions. Thibault Varin presented an application of ligand-based models in screening[7] campaigns at Lilly, and the discovery and initial optimization of selective RIO2 kinase inhibitors. Using chemical similarity, he selected from a set of virtual, robot-capable reactions a set of 8 compounds.…”
Section: Discussionmentioning
confidence: 99%
“…9)[7][13]. These were applied to predicting polypharmacology, modes-of-action for phenotypic screens, toxicity profiling, and selecting commercial compounds with diverse selectivity profiles for chemical archive enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Although these authors proposed an efficient algorithm for excluding records with errors of annotation, they did not explicitly investigate ways to compile data sets from databases of biologically active compounds specifically for the creation of predictive QSAR models. 1,4 Gao et al 5 reported a study of two sets of kinase inhibitors tested in two different assays. In contrast to our approach, the authors focused on the calculation of the concordance of kinase selectivity data for overlapping sets of compounds generated from four independent profiling sources but not on the analysis of the database contents for application to QSAR modeling.…”
Section: Comparison With Other Approaches From Literaturementioning
confidence: 99%
“…Several methods have been suggested to reduce this inconsistency in publicly available bioactivity databases. 1,4,5 Typically, these approaches are based on selecting only compounds investigated by a single team of authors to reduce the impact of different experimental conditions on the assay result.…”
Section: Introductionmentioning
confidence: 99%